Pengaruh Model Pembelajaran Kooperatif Tipe Make A Match Terhadap Pemahaman Siswa Dalam Pembelajaran PAI - Maria, Anly; Amani, Adinda Rania Khairunnisa (STAI Al-Musaddadiyah Garut, 2023)
Student comprehension is the ability to understand instructions or problems, interpret them, and rephrase them in one's own words. Currently, comprehension levels among students in Islamic Religious Education (PAI) are still low, as evidenced by students' inability to properly understand and explain the material presented, or to summarize it using their own words. Therefore, innovative and varied learning models are needed, such as the cooperative learning model